Dasatinib for treatment of CAR T-cell therapy-related complications - Jakob R Passweg; Dominik Heim; Katharina Baur; Astrid Beerlage; Anna S Poerings; Bastian Kopp; Michael Medinger; Jan C Dirks; Andreas Holbro (Journal for ImmunoTherapy of Cancer)
Cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS) are severe, potentially life-threatening side effects of chimeric antigen receptor T-cell (CAR T) therapy caused by the release of cytokines by proliferating and activated CAR T-cells. Current mainstay treatment includes interleukin-1 and interleukin-6 (IL-6) blockade and steroids. The use of steroids is still controversial, since they may have the potential to irreversibly damage CAR T-cells and thus increase the risk of relapse. Therefore, additional treatment options need to be explored. We report the successful treatment of a patient with a grade 3 CRS and grade 4 ICANS refractory to IL-6 blockade and steroids with the tyrosine kinase inhibitor dasatinib. The use of dasatinib for treatment of CAR T-cell therapy-related severe complications warrants further studies.